A review on the protective effects of honey against metabolic syndrome - Nur Zuliani Ramli; Chin, Kok-Yong; Khairul Anwar Zarkasi; Fairus Ahmad (MDPI, 2018)
Metabolic syndrome (MetS) is a cluster of diseases comprising of obesity, diabetes mellitus, dyslipidemia, and hypertension. There are numerous pre-clinical as well as human studies reporting the protective effects of honey against MetS. Honey is a nutritional food low in glycemic index. Honey intake reduces blood sugar levels and prevents excessive weight gain. It also improves lipid metabolism by reducing total cholesterol (TC), triglyceride (TG), low-density lipoprotein (LDL) and increasing high-density lipoprotein (HDL), which leads to decreased risk of atherogenesis. In addition, honey enhances insulin sensitivity that further stabilizes blood glucose levels and protects the pancreas from overstimulation brought on by insulin resistance. Furthermore, antioxidative properties of honey help in reducing oxidative stress, which is one of the central mechanisms in MetS. Lastly, honey protects the vasculature from endothelial dysfunction and remodelling. Therefore, there is a strong potential for honey supplementation to be integrated into the management of MetS, both as preventive as well as adjunct therapeutic agents.